Completing the Doha Round: now or never? - Bouët, Antoine; Elliott, Kimberly Ann (Inter-American Development Bank, 2006)
Reviving and completing the Doha Round will pose significant challenges for all the major trading nations in the WTO. This paper examines the causes of the ongoing negotiating impasse, and what needs to be done to restart the WTO talks by late 2006.